IMPLEMENTASI PROGRAM LIGHT ON (MENYALAKAN LAMPU UTAMA BAGI SEPEDA MOTOR PADA SIANG HARI) DI KOTA SEMARANG - Prabuninggar, Delima Anggasetya; Purnaweni, Hartuti; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Traffic problems facing today is the high number of traffic accidents on the highway. Through the Light On to turn on the headlights for motorcycles during the day, is expected to reduce the number of traffic accidents, especially in the Semarang City. The purpose of the study to describe and analyze the implementation of the Light On program (turn on the headlights for motorcycles during the day) in the city of Semarang. In answer to the problem and the purpose of this study, used the theory of George C. Edwarsds III combined with the theory of Donald S. Van Metter and Carl E. Van Horn in analyzing the factors that affect the implementation of the Light On program by using descriptive qualitative research methods to describe the actual implementation. In data collection, use the way through interviews, documentation, and observations relating to the title taken. The informants were selected include : Kasatlantas Polrestabes Semarang, Kanit Laka Satlantas Polrestabes Semarang, Kanit Dikyasa Satlantas Polrestabes of Semarang City, and 28 students of Diponegoro University who use motorcycle in Semarang City. The results showed that the implementation of the Light On is not optimal. There are many findings that actual discrepancy is not in accordance with what the goals of the Light Programme. It is recommended that a large commitment of each implementer to support the implementation of Light On program in Semarang City both in the budget provision and awareness in the applicationof the Light On program on field. It takes good communication coordination in order to support the success of the Light On program.